Evolution of the scholarly mega-journal, 2006–2017 - Bo-Christer Björk (PeerJ, 2018)
Mega-journals are a new kind of scholarly journal made possible by electronic publishing. They are open access (OA) and funded by charges, which authors pay for the publishing services. What distinguishes mega-journals from other OA journals is, in particular, a peer review focusing only on scientific trustworthiness. The journals can easily publish thousands of articles per year and there is no need to filter articles due to restricted slots in the publishing schedule. This study updates some earlier longitudinal studies of the evolution of mega-journals and their publication volumes. After very rapid growth in 2010–2013, the increase in overall article volumes has slowed down. Mega-journals are also increasingly dependent for sustained growth on Chinese authors, who now contribute 25% of all articles in such journals. There has also been an internal shift in market shares. PLOS ONE, which totally dominated mega-journal publishing in the early years, currently publishes around one-third of all articles. Scientific Reports has grown rapidly since 2014 and is now the biggest journal.